Coping Mechanisms and Stress Levels in the Climacteric Phase - I’ien Noeraini; Dayat Trihadi; Ellyzabeth Sukmawati; Danny Putri Sulistyaningrum; Achmad Solechan (Jurnal Bidan Cerdas, 2025)
Background: The climacteric phase is a critical transitional period often accompanied by physical, emotional, and psychosocial changes that may influence an individual’s ability to cope with stress. This study analyzed the relationship between adaptive coping mechanisms and stress levels among elderly retirees using a sequential mixed-methods design. Methods: A total of 169 respondents participated in the quantitative phase, followed by in-depth interviews with 10 key informants. Results: Fisher’s Exact Test revealed a significant association between adaptive coping and stress levels (p = 0.000; p < 0.05), while age and gender were not significant factors. Qualitative insights emphasized the vital role of social support from family, peers, and the community in strengthening adaptive coping and emotional well-being. Both findings indicates that enhancing adaptive coping and social support effectively reduces stress among older adults. Conclussion: These results highlight the need for community-based mental health initiatives and post-retirement support programs to promote resilience and improve the quality of life in the elderly.